Efektifitas Lembaga Perlindungan Anak Terlantar: Studi pada Panti Asuhan Suci Hati di Meulaboh, Kabupaten Aceh Barat (Effectiveness of Abandoned Child Protection Institutions: Study at Suci Hati Orphanage in Meulaboh, West Aceh Regency) - Djawas, Mursyid; Fajrina, Riska (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2019)
This article focuses on the study of UPTD LKSA Care Orphanage in Meulaboh West Aceh Regency as institution for abandoned children. There are three problems to be disscussed, namely: First, how roles and responsibilities of children's institution in the orphanage of Suci Hati. Secondly, how is the effectiveness of the children's institution in the orphanage of Suci Hati to protect the neglected child. Third, how does the view of Islamic law of the abandoned Child protection Agency. In the authors ' discussion using the research type field Research; observation, interviews and documentation. Based on the results of the study, children's institution in the orphanage of Suci Hati has achieved effective (successful) in general to meet the needs and protect the displaced children Leader of the institution. In Islam, the right of children is the obligation of Allah SWT. So, parents, people, and governments who are able to run it will get reward rewards from Allah SWT. The one who ignored it will be given difficulties in the world and the hereafter. The author suggests for all parties concerned in protecting the child to pay more attention to children in the orphanage institutions, especially in giving compassion and fulfillment of daily needs to the children Improving the welfare of children.